تحديات التدقيق المالي في ظل التشغيل الإلكتروني دراسة حالة ديوان الترقية والتسيير العقاري الأغواط - شتوح محمد صلاح الدين; بن الجمعي عبد الرحمان الطاهر; جقيدل يحي (جامعة عمار ثليجي الاغواط, 2022)
In this study, we tried to address the challenges of Statutory auditor in light of electronic operations. Where we used the personal interview and documents tools in order to reach a clearer understanding of the problem of how can electronic operation strengthen the role of the account keeper in the institution? Relying on the case study and based on the findings, we find that electronic operation plays a major role in achieving the audit task in terms of efficiency, effort and effectiveness, which increases the reliability and credibility of information and financial statements.